Morphological and Syntactic Deficiencies in EFL Narrative Writing: A Surface Strategy Taxonomy Analysis of Past Tense Errors - Pratiwi Ayu Lestari Mohamad (PT MEDIA JURNAL DAN PENDIDIKAN, 2025)
Mastering the simple past tense in narrative writing remains a significant grammatical hurdle for English as a Foreign Language (EFL) learners due to the complexities of verb inflection. This study investigates the specific morphological and syntactic errors in using the simple past tense among tenth-grade students, aiming to identify the types and dominant categories of these deficiencies. Utilizing a descriptive qualitative design, data were collected through a 90-minute narrative writing test from a random sample of 20 students at SMA Negeri 1 Popayato. The identified grammatical deviations were analyzed and categorized using Dulay’s Surface Strategy Taxonomy. The results revealed a total of 374 grammatical errors. Misformation was the overwhelmingly dominant error, accounting for 62% (231 errors), primarily driven by the misconjugation of irregular verbs and incorrect 'to be' usage. This was followed by errors of omission at 24% (90 errors), addition at 13% (48 errors), and misordering at 1% (5 errors). In conclusion, the high frequency of misformation and omission indicates a fundamental gap in students' understanding of past tense morpho-syntax, strongly influenced by first language (L1) interference where tense markers do not exist. This necessitates targeted pedagogical interventions, such as intensive verb-drilling and contextual grammar exercises, to improve EFL narrative writing accuracy.